Defining antibiotic resistance-towards international harmonization. (May 2014) - Kahlmeter, Gunnar
Abstract Antimicrobial susceptibility testing with phenotypic methods requires breakpoints, i.e. a minimum inhibitory concentration (MIC) categorizing micro-organisms into susceptible, intermediately susceptible, and resistant for the relevant antimicrobial agent. Determinations of breakpoints require tools such as the understanding of dosing, MIC distributions of organisms without resistance mechanisms, pharmacokinetics, pharmacodynamics, and of clinical outcome in defined clinical situations. Several European countries (France, Germany, Norway, Sweden, the Netherlands, and UK), have national breakpoint committees, often with 20–30 years of experience and tradition. These committees now co-operate under the umbrella of the European Committee on Antimicrobial Susceptibility Testing (EUCAST), organized by The European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and the European Centre for Disease Prevention and Control (ECDC). Together with the European Medicines Agency (EMA), EUCAST determines breakpoints for existing and new antibacterial and antifungal agents. Moreover, EUCAST has developed a disk diffusion antimicrobial susceptibility testing method which is now, together with the new European breakpoints, being implemented in many countries both inside and outside Europe.